Very early onset of coronary artery aneurysm in a 3-month infant with Kawasaki disease: a case report and literature review - Wenyan Jiao; Li Wei; Fuyong Jiao; Dorina Pjetraj; Jianying Feng; Jvyan Wang; Carlo Catassi; Simona Gatti (BMC, 2023)
Abstract Background Kawasaki disease (KD) is a medium vessel vasculitis, of unknown etiology, typically presenting in children younger than 5 years of age. Prolonged fever (at least five days) is a major clinical criterion of KD, while cardiac involvement may occur in up to 25% of patients, generally in the second week of the disease. Case presentation We describe the case of KD developing in a 3-month infant, with an early occurrence of coronary artery aneurysm after only 3 days of fever, complicated by thrombosis, requiring aggressive treatments. Conclusions Time of development of cardiac complications can be different in young infants with KD and both diagnostic criteria and treatment indications should be individualized in this class of age.